A high strength and conductivity bulk Magnéli phase Ti4O7 with superior electrochemical performance. Issue 17 (1st September 2022) - Liu, Hui Jun; Luo, Meng Qi; Yang, Ling Xu; Zeng, Chao Liu; Fu, Chao
Abstract: Here we report for the first time that Magnéli phase Ti4 O7 electrode with super performance is successfully prepared by hot-pressed sintering of single-phase submicron Ti4 O7 powders. The microstructure, mechanical properties, electrical conductivity and electrochemical performance of the Ti4 O7 electrodes were also investigated. Results show that the compact and homogeneous bulk Ti4 O7 without evident defects such as pores and cracks is achieved when the submicron Ti4 O7 powder was sintered at 1200 °C for 0.5 h. As a result, the bulk density of the Ti4 O7 reaches its theoretical value (4.323 g cm −3 ). Additionally, it has excellent physical and chemical properties, including the mean values of hardness and Young's modulus of 15.20 ± 0.42 and 247.40 ± 6.70 GPa, respectively, the Vickers-hardness of 1165.5 ± 9.5 HV, the highest known conductivity of 1252.5 S cm −1, and the widest known electrochemical stability window of 4.19 V in 1 M NaCl solution.